The occurrence of taeniids of wolves in Liguria (Northern Italy) - Gori, Francesca; Armua Fernandez, Maria Teresa; Milanesi, Pietro; Serafini, Matteo; MAGI, MARTA; Deplazes, Peter; MACCHIONI, FABIO (International Journal for Parasitology: Parasites and Wildlife, 2015)
Canids are definitive hosts of Taenia and Echinococcus species, which infect a variety of mammals as intermediate or accidental hosts including humans. Parasite transmission is based on domestic, semi-domestic and wildlife cycles; however, little is known of the epidemiological significance of wild large definitive hosts such as the wolf. In this study, 179 scats of wolves (. Canis lupus italicus) collected throughout the Italian region of Liguria were analyzed for the detection of taeniid infection. Taeniid egg isolation was performed using a sieving/flotation technique, and the species level was identified by PCR (gene target: 12S rRNA and nad 1) followed by sequence analyses. Based on sequence homologies of ≥99%, Taenia hydatigena was identified in 19.6%, Taenia krabbei in 4.5%, Taenia ovis in 2.2%, Taenia crassiceps in 0.6%, Hydatigera taeniaeformis in 0.6% and Echinococcus granulosus in 5.6% of the samples. According to these results, Canis lupus italicus can be considered as involved in the wild (including cervids and rodents) and semi-domestic cycles (including sheep and goats) of taeniids in this area.